2015
DOI: 10.1002/aenm.201500279
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Underlying Processes Involved in Light Soaking Effects and Hysteresis Phenomena in Perovskite Solar Cells

Abstract: continuously increase with light illumination while the shortcircuit current ( J SC ) experiences a quick increase and then a decrease upon light exposure. The C -V measurements fi nd that light soaking can decrease the charge accumulation at the electrode interfaces. Essentially, the light soaking-decreased charge accumulation at electrode interface can be attributed to following two possible processes. First, the photogenerated carriers can neutralize the interfacial defects at electrode interface upon light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
278
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(296 citation statements)
references
References 40 publications
(87 reference statements)
16
278
1
1
Order By: Relevance
“…[88] This rising behavior or PL enhancement (Figure 4e), is also obtained in inorganic semiconductor QDs, e.g., CdSe QDs, [76] ZnS-capped CdSe QDs, [78] etc. This PL rising behavior has been attributed to the migration of charge carriers, followed by a trap-filling process at energetically shallow defects within the film.…”
Section: Pl Rising Mechanismmentioning
confidence: 52%
“…[88] This rising behavior or PL enhancement (Figure 4e), is also obtained in inorganic semiconductor QDs, e.g., CdSe QDs, [76] ZnS-capped CdSe QDs, [78] etc. This PL rising behavior has been attributed to the migration of charge carriers, followed by a trap-filling process at energetically shallow defects within the film.…”
Section: Pl Rising Mechanismmentioning
confidence: 52%
“…It can be observed that both S1 and S3 devices exhibit good stability, and for both devices with alternating light/dark periods we can observe some recovery of the effi ciency upon illumination on the next day. Improvement in the device performance after light soaking has been reported in perovskite devices with different architecture, [35][36][37] which was attributed to the reduced trap density under illumination. [ 35 ] We observe some initial improvement in the effi ciency without heating, followed by decrease and then recovery upon illumination next day, and this effi ciency increase is more pronunced in aged cells.…”
Section: Resultsmentioning
confidence: 99%
“…Improvement in the device performance after light soaking has been reported in perovskite devices with different architecture, [35][36][37] which was attributed to the reduced trap density under illumination. [ 35 ] We observe some initial improvement in the effi ciency without heating, followed by decrease and then recovery upon illumination next day, and this effi ciency increase is more pronunced in aged cells. It is expected that aged cells would have higher density of defects and traps and thus may exhibit improvement in performance upon illumination after storage in the dark.…”
Section: Resultsmentioning
confidence: 99%
“…As aforementioned, the photocatalytic activity of SnO 2 is less pronounced due to a higher band gap of~3.8 eV, which is favorable to the device's stability when exposed to UV light. In planar or mesoporous PSCs, hysteresis effect in current-voltage characterizations is a common phenomenon observed under different conditions including scan directions and rates, as well as applying bias voltage and light soaking prior to measurement [42,43]. To date, many reasons have been indicated to be the causes of hysteresis behavior, such as ion migration and transient ferroelectric polarization [44].…”
Section: Resultsmentioning
confidence: 99%